Practical Approaches in Mill Building Columns Subjected to Heavy Crane Loads - Bendapudi, Kasi V. (Engineering Journal, 1994)
Since the turn of this century, the amount of analytical and experimental research in the area of column design has been extensive. While the information and results of such research is scattered and narrowly focused in very specialized areas, identification of this vast amount of relevant information available is often difficult. There is no legal code governing the design of heavy mill building columns and the designs are based on experience and judgment. Additionally, there are varying types of mill building columns due to assumptions and geometry. This has led to a design practice that varies from one designer to another, based on their experience and knowledge of the mill buildings. For a practicing engineer it is essential to analyze, integrate, and establish a logical and comprehensive design methodology and procedures. It is not possible to establish one generic approach applicable to all types of mill building columns. It is rather easier to deal independently with each type of these complex structural elements in achieving this goal. This paper presents a design methodology and procedures for "heavy mill building columns" subjected to heavy crane loads. For the purpose of this paper heavy crane loads are defined as loads imparted by cranes with lifting capacity ranges from 100 tons to 500 tons such as hot metal cranes. These columns consist of two or more shafts and are laced together to achieve composite behavior. The column bases are fully fixed and the roof trusses are simply supported at the top of the building shaft. The bottom chords of the trusses are braced the full length of the building. Other types of mill building columns are not included in the scope of this paper. Therefore, the procedures and methodology presented herein may not be directly applicable to any other type of mill building column.